Fun and useful apps: female identity construction and social connectedness using the mobile phone - Rickard, S.; Lloyd, Clare (ANZCA, 2012)
This article explores the domestication of mobile technologies by women and how their identities, as seen through their choices of apps, are interrelated to their social connectedness. Building on existing gender, intimacy and mobile communications literature, this paper provides a needed overview of how women are strategically deploying the use of ‘apps’ on their smart phones in both ‘fun’ and ‘useful’ ways. Two groups are being analysed in this article. The first comprises women who only use a mobile single Internet connection, identified as ‘Single Connectors’. This group is contrasted with a second group who use multiple Internet connections, identified as ‘Triple Connectors’. In this article we playfully name the social seeking Triple Connectors Social Butterflies and the mobile Internet Single Connectors have been identified as Information Seeking Consumers. ‘Social networking’ was identified as a ‘fun’ app rather than a ‘useful’ app by both groups of female connectors; what does this say about women and their definitions of leisure? Are women still viewing networking as part of their commitment to emotional labour rather than something that is ‘useful’? What might this tell us about women and their ability to build intimacy, identity, and social connectedness using the mobile phone?